Feasibility of Material and Presentation of Arabic Language Book - Nazila, Nazila R Dewi Tahir; M. Afif Amrulloh; Zulhannan (Jurusan Pendidikan Bahasa Arab, 2025)
In general, there are many textbooks in Indonesia that have not met the eligibility standards, especially from the language aspect, which can hinder the effectiveness of student learning. This problem can have an impact on understanding the material and can reduce student motivation to learn. Based on these problems, this study aims to analyze the feasibility of language in Arabic Language Book 1 published by Tiga Serangkai, in accordance with the standards set by the National Education Standards Agency (BSNP) and also using the theory of Muhamad Abed Al Jabiri. This research uses a qualitative method with the type of library research. Data were collected through documentation techniques and interviews with Arabic language teachers, then analyzed using content analysis techniques. The results of the analysis show that this book is in accordance with BSNP standards, especially in terms of the use of language that is suitable for the level of student development, is communicative, and has a coherent and orderly flow of discussion. This book is also in accordance with Al-Jabiri's approach, namely the bayani method reflected in the presentation of memorization and fixed texts, the irfani method through affective experiences, and the burhani method in logical structures. The language used is easily understood by madrasah tsanawiyah students because it is close to everyday life. The material is organized systematically, equipped with vocabulary and exercises that support learning. The book also shows a systematic and consistent flow of material delivery between chapters, strengthening the development of student reasoning. Therefore, this book is considered feasible to use in learning Arabic in madrasah tsanawiyah because it is able to assist students in learning, with a note that more attention needs to be paid to providing mufrodat that are more relevant and familiar to students.